The Impact of Unidentified Consumer Transfers on Accounts Receivable Reconciliation Accuracy in the Digital Era: A Case Study - Meysia Amalia; Zahri Fadli; Minasari Nasution (Journal of Finance Integration and Business Independence, 2025)
This study aims to determine the impact of unidentified consumer transfers on the accuracy of accounts receivable reconciliation in the digital financial system at PT Cakrawala Citramega Multifinance. This phenomenon arises when consumers make bank transfers without including adequate information, such as contract numbers or names that match the system records. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The results indicate that unidentified transfers delay the reconciliation process because payments cannot be automatically matched with the consumers’ receivable accounts. This leads to delays in financial reporting and a higher risk of recording errors. Time-consuming clarifications and high transaction volumes are also major challenges. Therefore, improvements in transaction identification systems and consumer education are needed so that payment information can be recognized more accurately.